(untitled) (MAUSAM, 1982)
The large scale circulation features which determine rainfall anomalies in South Asia are discussed. Singularities In. rainfalls and typhoon activity supplemented changes in global circulation are shown. The Interaction of planetary flows with Tibet is supposed to be a primary source for rainfall anomalies in South Asia as well as for aridity of the Middle East and North Africa.